Diretrizes para elaborar indicadores de desempenho de internacionalização da educação superior: um estudo de caso na Unila - Arana, Roberta Soato (2023)
The internationalization of Higher Education is a topic that encompasses academic and administrative areas of institutions. In recent decades, it has become an important element for institutional growth and a challenge to monitor, measure and evaluate its policies, programs, strategies and actions. This challenge has encouraged the development of a range of tools, including institutional performance indicators with the function of contributing to the self-assessment of the internationalization of universities. From this perspective, the research sought to answer the following problem: what are the guidelines for developing performance indicators related to Unila’s own conception of internationalization? To answer this, the objective of the research was to design guidelines for preparing these indicators aimed at Unila’s internationalization. The institution was defined due to its innovative character in proposing internationalization focused on Latin America and the Caribbean and for oscillating between first and second place among public universities with the largest number of international students in Brazil. As a starting point for the research, exploratory research was carried out, using a literature review. The procedure adopted for data collection was case study, documentary research and participant observation. In the analysis and interpretation of data, a qualitative approach was used. As a result, the research suggested a total of eighty-one guidelines, divided into four dimensions, namely: i) higher administration composed of the subcategories: policies, management and infrastructure with nineteen guidelines; ii) internal and external community that encompasses the subcategories: students, teachers, administrative technicians in education and external community distributed across twenty-three guidelines; iii) solidarity cooperation (national and international relations) with the subcategories partnerships for cooperation; courses, programs, projects and actions in cooperation, linguistics and interculturality with twenty-six guidelines; and iv) supportive sharing of knowledge with the academic dissemination subcategory, observing participation in events and publications with thirteen guidelines. The guidelines highlighted in the research are aligned with a transversal internationalization in accordance with Unila's mission, vocation, purposes and institutional objectives; aimed at solidary and horizontal cooperation between Latin American and Caribbean countries, Mercosur and the Triple Border region. It is expected that the result of the work can contribute to the institution's management in the task of measuring, evaluating and monitoring the development of its internationalization.